Reducing Point-of-care Blood Gas Testing in the Intensive Care Unit through Diagnostic Stewardship: A Value Improvement Project. Issue 4 (July 2020) - Tchou, Michael J.; May, Sally; Holcomb, John; Tanner-Edwards, Ethan; Good, Kathy; Frazier, Matthew; Stalets, Erika L.; Dewan, Maya
Abstract : Introduction: Overutilization of point-of-care (POC) testing may reduce the overall value of care due to high-cost cartridges, need for staff training, and quality assurance requirements. Methods: The Diagnostic Stewardship group at Cincinnati Children's Hospital Medical Center assembled a multidisciplinary team to reduce the use of POC blood gas testing by 20% in the pediatric intensive care unit (PICU). Key drivers of test overutilization included poor knowledge of cost, concern with testing turnaround time, and a lack of a standard definition of when a POC test was appropriate. We calculated weekly the outcome measure of POC blood gas tests per PICU patient-day and a balancing measure of blood gas result turnaround time using data extracted from the electronic medical record. Interventions focused on staff education, the establishment of a standard practice guideline for the use of POC testing, and improving turnaround time for laboratory blood gas testing. Results: Over the baseline period starting July 2016, a median of 0.94 POC blood gas tests per PICU patient-day was ordered. After initial staff training, the rate was reduced to 0.60 tests per PICU patient-day and further reduced to 0.41 tests per PICU patient-day after a formal policy change was adopted. We have sustained this rate for 15 months through June 2018. Institutional direct cost savings were estimated to be $19, 000 per year. Conclusions: Our improvement initiative was associated with a significant and rapid reduction in the use of POC testing in the PICU. Interventions focused on cost awareness, and a formal guideline helped establish a consensus around appropriate utilization. Abstract : Supplemental Digital Content is available in the text.